Impact of Maternal Nutritional Status on Morning Sickness Severity and Fetal Health: A Correlational Study - Suriati, Israini; Juliani, Reski (Media Publikasi Cendekia Indonesia, 2025)
Morning sickness is a common symptom of pregnancy that occurs in the first trimester, characterized by nausea, vomiting, and fatigue due to hormonal changes such as hCG and estrogen. Although physiological, this condition can interfere with the mother's nutritional intake and have a negative impact on fetal health, especially if it is severe and prolonged. Masih there are still many pregnant women who face obstacles in meeting nutritional needs and optimally handling morning sickness. This study aims to determine and analyze the relationship between the severity of morning sickness, nutritional status of pregnant women, and fetal health. Method This study used a quantitative design with a cross-sectional approach. A sample of 100 pregnant women who experienced morning sickness in the first or second trimester, selected by purposive sampling at five Health Centers in Palopo City during July–November 2024. Data were collected through questionnaires and interviews, then analyzed using the Chi-square test with a significance level of p <0.05. A total of 36% of respondents had good nutritional status, 36% were undernourished, and 28% were overnourished. The severity of morning sickness was categorized as mild in 28% of respondents, moderate in 40%, and severe in 32%. Fetal health was considered good in 58% of respondents and poor in 42%. There was a statistically significant relationship between maternal nutritional status and the severity of morning sickness (P-value = 0.005), as well as between nutritional status and fetal health (P-value = 0.003). Additionally, a significant association was found between the severity of morning sickness and fetal health.